A new fluorine-containing star-branched polymer as electrolyte for all-solid-state lithium-ion batteries. (20th June 2018) - Xu, Hao; Wang, Ailian; Liu, Xu; Feng, Di; Wang, Shi; Chen, Jie; An, Yan; Zhang, Liaoyun
Abstract: The trade-off between ionic conductivity and mechanical strength is still a great challenge for all-solid-state polymer electrolyte. Herein, a novel structure-controlled fluorine-containing star-branched polymer (HBPS-(PTFEMA- b -PPEGMA)27 ) with a hyperbranched polystyrene core and polytrifluoroethyl methacrylate-block-poly (ethylene glycol) methyl ether methacrylate arms is synthesized by atom transfer radical polymerization. Combining the good mechanical strength of fluorine-containing segments and flexible property of PEG segments, the prepared HBPS-(PTFEMA- b -PPEGMA)27 /LiTFSI solid polymer electrolyte can form flexible transparent self-standing membrane and exhibits the high ionic conductivity of 2.4 × 10 −5 S cm -1 at 25 °C, as well as good thermal stability with the thermal decomposition temperature of 374.7 °C. It also possesses a wide electrochemical window of 4.9 V and good interfacial compatibility. Moreover, the Li/LiFePO4 cell based on this solid state star-branched polymer electrolyte membrane delivers a high discharge capacity of 147.2 mAh g −1 under a current density of 0.1C at 60 °C. Graphical abstract: Image 1 Highlights: A fluorine-containing star-branched polymer is synthesized via ATRP polymerization. The prepared electrolyte membranes show great flexibility and transparency. The electrolyte membrane has a wide electrochemical window of 4.9 V. The highest discharge capacity can reach 147 mAh g −1 under 0.1C at 60 °C.